(untitled) (Diametros, 2005)
Branching is a set-theoretical model of reality that is in accord with contemporary physics. This structure is also a model for some logical calculi. However, if the formal language defined on the basis of branching is to correspond to our ways of speaking about possible events, a number of issues must be clarified. All of them are connected with the notion of possibility that is employed in this language. Yet the apparent need to supplement this language with an additional notion of possibility means that branching ceases to be attractive as a candidate for a model of physical reality, as it contains considerably more elements than we would like to see in reality. Thus, the connection between this logical tool and ontology becomes questionable.